Disrupted Patterns of Rich-Club and Diverse-Club Organizations in Subjective Cognitive Decline and Amnestic Mild Cognitive Impairment - Xue, Chen; Sun, Haiting; Hu, Guanjie; Qi, Wenzhang; Yue, Yingying; Rao, Jiang; Yang, Wenjie; Xiao, Chaoyong; Chen, Jiu; , the Alzheimer’s Disease Neuroimaging Initiative (Frontiers in Neuroscience, 2020)
Background: Subjective cognitive decline (SCD) and amnestic mild cognitive impairment (aMCI) were considered to be a continuum of Alzheimer's disease (AD) spectrum. The abnormal topological architecture and rich club organization in brain functional network can reveal the pathology of AD spectrum, however, few study has explored the disrupted patterns of diverse club organization and the combination of rich and diverse club organization in SCD and aMCI. Methods: We collected resting-state functional magnetic resonance imaging (rsfMRI) data of 19 SCD, 29 aMCI, and 28 healthy control (HC) from the Alzheimer's Disease Neuroimaging Initiative. Graph theory analysis was used to analyze the network metrics, rich club, and diverse club organization simultaneously. Results: Compared to HC, aMCI group showed altered small-world and network efficiency while SCD group remained relatively stable. The aMCI group showed reduced rich club connectivity compared to HC. In addition, aMCI group showed significant increased feeder connectivity and decreased local connectivity of diverse club compared to SCD group. The overlapping nodes of rich and diverse club showed significant difference in nodal efficiency and shortest path length (Lp) between groups. Notably, the Lp of overlapping nodes in the SCD and aMCI groups were significantly associated with episodic memory. Conclusions: The present study demonstrates the network properties of SCD and aMCI have varying degrees of damage. The combination of rich and diverse club can provide a novel insight into the pathological mechanism of AD spectrum. The altered patterns in overlapping nodes might be potential biomarkers in the diagnosis of AD spectrum.